The birth and growth of toshiba's laptop and notebook computers: A case study in Japanese corporate venturing - Abetti, Pier A. (Journal of Business Venturing, 1997)
This case study presents the “under the table” birth, accelerated growth, and ultimate success of two major technological and market innovations: (1) the Toshiba laptop computer, a project vetoed twice by corporate headquarters, and (2) the notebook computer, a project hidden from headquarters. Because of the vision, persistence, and championing efforts of a team of passionate Japanese corporate entrepreneurs, a new business was created that is now part of Toshiba's mainstream operations and that has become a significant contributor to the growth and profitability of the corporation. We follow the evolution of this corporate venture from initial failures in 1978 to the success of the laptop computer, first in Europe (1985), then in the United States, and finally in Japan. This was followed by the reincorporation of the venture in the corporate “mainstream” (1987), the worldwide success of the notebook computer (1989), and the continued growth of the business in parallel with repeated promotions of the entrepreneurs. First, a framework is presented for interpreting the case within current theories and practices of the management of innovation and the processes of championing innovative corporate ventures. This framework is expanded to include recent studies on how major corporations have achieved worldwide leadership in high-tech markets. Second, using the analogy of human life from conception to adulthood, the key phases, events, and entrepreneurial actions of Toshiba's PC business are summarized in Table 1. Third, the theoretical framework is applied to a discussion of the unusual aspects of this case. Fourth, we analyze the business strategy and the technology strategy developed by Toshiba. Finally, we summarize the cultural and organizational context of Toshiba as well as other critical factors that contributed to the enduring success of this corporate venture. There are four aspects, in addition to the international setting, that make this case interesting for both scholars and practitioners: (1) the “under the table” development of both the laptop and notebook, (2) the unexpected success of the first product, followed by a second success, (3) the evolution of champi oning at various organizational levels, and (4) the continuity of the strategic vision for Toshiba's information systems business from 1978 to the present, and how this vision was translated into specific business and technological strategies. From the perspective of management of innovation, the successes of both the laptop and the notebook computers were due to the “back to the future“ market research and design process summarized in Table 2. This process, where market requirements drive the design process, was developed by the lead entrepreneur, Tetsuya Mizoguchi, after repeated failures of the conventional process, where the results of R&D drive the design and productspecifications, regardless of market requirements. From the perspective of the championing processes, we can observe both bottom-up and top-down roles (Day 1994): Mizoguchi was the product champion and Nishida the marketing champion in Europe, while General Manager Koga protected Mizoguchi from interference by headquarters; executive champion Mizushima orchestrated the difficult transition of the venture into a corporate mainstream operation. The evolution of the championing process is summarized in Table 3, using the Venkatamaran et al. model (1992). We conclude that the most appropriate model for interpreting this case is a combination of the Day and Venkatamaran et al. models, which emphasizes both multiple championing roles and the transfer of the lead role from one champion to another during the corporate entrepreneurship process. The business strategy and market and technological strategies developed by Toshiba for achieving worldwide leadership in the portable PC market are summarized in Figures 1 and 2. More broadly, the process and critical factors that determined Toshiba's success can be visualized according to Figure 3. The corporate entrepreneurs and champions were driven away from mainframes by a vision of distributed and interconnected computing that compelled them to focus on personal computers. This focus determined the winning business strategy (fully compatible portable units) which in turn determined the technological and market strategies (miniaturization and complementarity to IBM). At the same time, this focus allowed the entrepreneurs to concentrate their scarce resources on the “back to the future” design process and develop unique core competencies. This coupling of winning strategies with unique core competencies made possible Toshiba's potential leadership in the marketplace. Actual leadership was achieved through continuous, step-by-step learning by doing and through market feedback that further reinforced the adopted strategies and enhanced the core competencies. Six critical factors contributed to the long-term success of the corporate venture: (1) the venture had the potential to achieve worldwide leadership in a mainstream area of the corporation, (2) the PC market in Europe and the United States (but not initially in Japan) was fragmented and highly receptive to unique innovations, (3) the corporate entrepreneurs were driven by a long-range vision of the business, with focused strategies and well-defined objectives, (4) the entrepreneurs were persistent and undeterred by repeated failures in the marketplace and by the distrust and hostility of headquarters, (5) the organizational context, because of slack internal controls, allowed the diversion of funds and manpower to the “under the table” venture and, finally (6) the role of entrepreneurs evolved from underground innovators to product, executive, and corporate champions in order to reinforce, broaden, and implement their vision.